Increased Marketing of Instant Ginger Production by Using Social Media and Improved Packaging Design in Harjomulyo Village, Silo District, Jember Regency - Reni Umilasari (OJS Universitas Muhammadiyah Gresik, 2020)
Ginger (Zingiber officinale) is a rhizome plant that is very popular as a spice and medicinal ingredient. The use of ginger itself varies depending on culture. While in Indonesia, ginger roots and rhizomes are widely used for treatment. Starting from crushed, made into tea, until smeared for healing then the use of ginger root is very thick in the community environment. Seeing how popular and the various benefits that exist in the ginger plant make masangka in Harjomulyo Village, Silo District, Jember Regency, especially the women of the Al-Hasan Muslimatan Group held an instant ginger powder production activity. This is because Harjomulyo Village is a very strategic plantation area for ginger cultivation so that this plant is quite abundant in the Harjomulyo Village area. The problem that arises that is the marketing of instant ginger production has not been effective. This is due to the absence of special media as a means of promotion / marketing. Until now marketing techniques have only been carried out manually by word of mouth so that not many people know that abundant ginger plants in Harjomulyo Village are produced to become instant ginger ready to drink or as a mixture of drinks or other food ingredients. Therefore there is a need for training and assistance related to production and marketing activities in the hope that it can improve the packaging design to be more attractive so that it has a high selling value; use social media as a new means of marketing instant ginger products for women from the Al-Hasan Muslimatan Group Harjomulyo Village; using Instagram as a marketing tool; as well as using the Android-based